Evaluation of Toxicological Effects of Brown Seaweeds: Part I. (Biological Sciences - PJSIR, 2022)
For determining moisture and ash [17], one gram sampleof each seaweed was kept in oven at 110°C for 6 hr. Cooled indesicator to constant weight. Finally moisture was calculated.The toxicity of Cystoseira barbata, Padina pavonia andSargassum boveanum was determined by the administrationof dried powder via oral route [18] in normal albino mice,